Investigating diesel market integration in France: Evidence from micro data (2017)
We use station-level daily price observations collected over a period of eight years to study the extent of diesel market integration in France. The empirical analysis starts off by examining the time-series properties of diesel price ratios, and then assesses how geographical separation and petrol station characteristics affect the speed of adjustment of prices to exogenous shocks. Our findings reveal that the great majority of diesel price ratios maintain stable long run relationships. We also find that while price ratios take longer to adjust for pairs of petrol stations that are farther apart, adjustment is quicker when pairs of petrol stations provide the same range of services, and when they belong to the same owner. © 2017 Elsevier B.V.